2001
DOI: 10.1071/wr99060
|View full text |Cite
|
Sign up to set email alerts
|

Review of the effects of organophosphorus and carbamate insecticides on vertebrates. Are there implications for locust management in Australia?

Abstract: The Australian Plague Locust Commission uses the organophosphorus insecticide fenitrothion to control locust population increases across 2000000 km2 of eastern Australia. Although the impact of fenitrothion on non-target invertebrates has been studied, effects on vertebrates are largely unquantified. Lethal and sublethal impacts on vertebrates are a consequence of the use of organophosphorus and carbamate insecticides. Information detailing the effects of exposure on free-living animals, particularly for herpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 88 publications
0
39
0
Order By: Relevance
“…Indeed, increasing chemical pesticide resistance has become a major obstacle to migratory locust control in recent years (Yang et al 2009). During an outbreak in Australia in which locusts were sprayed with organophosphorous insecticides, locusts in weakened or dying states were the primary food item for several bird species (Story and Cox 2001). In fact, due to concerns about insecticide toxicity, humans are discouraged from eating locusts in outbreaks that have been treated with insecticides (Showler 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, increasing chemical pesticide resistance has become a major obstacle to migratory locust control in recent years (Yang et al 2009). During an outbreak in Australia in which locusts were sprayed with organophosphorous insecticides, locusts in weakened or dying states were the primary food item for several bird species (Story and Cox 2001). In fact, due to concerns about insecticide toxicity, humans are discouraged from eating locusts in outbreaks that have been treated with insecticides (Showler 2009).…”
Section: Discussionmentioning
confidence: 99%
“…However, an understanding of the appropriate assay conditions for individual species is required to measure ChE activity as well as obtain the most reliable results from reactivation. Despite this, there is little published information on ChE activity in species of Australian native birds, or Australian terrestrial vertebrates generally (Story and Cox 2001;Bain et al 2004;Fildes et al 2006;Buttemer et al 2008). This lack of data must be remedied for the biomonitoring of sublethal pesticide effects to be incorporated into risk assessments of anti-ChE chemical exposure.…”
Section: Introductionmentioning
confidence: 99%
“…The aerial spraying could have influenced fledgling quality negatively through direct non-lethal toxic effects (Grue & Shipley, 1981;Day et al, 1995) or by reducing food availability (mainly Orthoptera) along the nestling growth period (Howe et al, 1996;Boatman et al, 2004;Morris et al, 2005); a combination of both factors may have contributed to the observed effects on breeding performance. We did not study the extent of nestling exposure to the insecticide but the presence of sprayed fields within the main foraging areas of some colonies suggests the possibility of negative effects of malathion application due to the consumption of contaminated prey (Story & Cox, 2001). In our study area, many grasshoppers were found dying or with reduced mobility in the malathion-treated fields.…”
Section: Discussionmentioning
confidence: 53%
“…However, their effect on wild avian populations is still poorly understood (Sanchez-Hernandez, 2001;Story & Cox, 2001). The attempts to extrapolate the results derived from laboratory research to field conditions have usually failed even at the organism level.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation